Strategies of Indonesian Islamic Religious Education Teachers in Improving Student Learning Motivation in Limited Face-to-face Learning during the Pandemic - Salmah Fa’atin,; Ulfah Rahmawati,; Nurul Hana, (Human Sustainability Procedia, 2022)
This article discusses the efforts of Islamic Religious Education teachers in Indonesia in increasing student learning motivation during the pandemic. This study aims to determine: (1) Policies and stages of implementation of limited face-to-face learning in Indonesian schools (2) The efforts of Islamic Religious Education teachers in Indonesia in increasing students' learning motivation during the pandemic. This study uses a type of field research with a descriptive qualitative approach. The research subjects were the principal, PAI teachers, and students. The data collection uses observation, interview, and documentation techniques. The stages of data analysis in this study consisted of data reduction, data presentation, and verification and conclusion drawing. The results of this study indicate that:1). The implementation of limited face-to-face learning in Indonesian schools is a policy of the principal based on a joint decree of four Ministers. The stages of implementing limited face-to-face learning are carried out based on aspects of planning, process, and evaluation. 2). The efforts of Islamic Religious Education teachers in increasing student learning motivation during the pandemic are: First, there are fun learning models, students feel happy, excited, and motivated in participating in learning. Second, with the use of multimedia, students can more easily understand the material being taught, because students can also listen audio-visually. Third, effective communication between teachers and students makes teaching and learning activities in the classroom no longer a boring routine for students, especially during a pandemic. Fourth, with assignments given by educators, students become more independent and responsible for the tasks given, and can foster discipline in students to be more active in learning.